2007
DOI: 10.1039/b704075j
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of biomolecules with inorganic materials: principles, applications and future prospects

Abstract: The goal of this article is to overview the current understanding of biomolecule-inorganic materials interactions; to identify the 'rules' that govern interaction; to highlight the drawbacks of the present approaches and outline future challenges and opportunities.Please check this proof carefully. Our staff will not read it in detail after you have returned it. Translation errors between word-processor files and typesetting systems can occur so the whole proof needs to be read. Please pay particular attention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
80
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 86 publications
1
80
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8] . A comprehensive analysis of the properties of these systems could be very useful for designing highly biocompatible materials and specific biosensors [9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] . A comprehensive analysis of the properties of these systems could be very useful for designing highly biocompatible materials and specific biosensors [9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…biosensors and bioarrays [21][22][23][24], whilst peptide-inorganic interfaces offer novel means of materials synthesis and nanoscale fabrication [25][26][27][28]. The common theme underpinning these disparate research avenues is the desire to develop, at the molecular level, a detailed and accurate description of the intermolecular interactions responsible for these phenomena and to thereby elucidate the relationship between peptide structure and function.…”
Section: Molecular Physics Gly˙ala˙crystal˙redraftmentioning
confidence: 99%
“…Although there are limitations to this approach, 60,61 a number of metal-binding peptides (M-BPs) [62][63][64][65] and metal oxide-binding peptides (MO-BPs) 46,58,[66][67][68][69][70] have been identified that have either been shown to have an affinity for the surface they were isolated from or have been shown to influence the growth of their respective metal or metal oxide. The identification of ZnO-binding peptides (ZnO-BPs) and understanding how they adhere to the surface of ZnO is potentially useful for the construction of artificial biomaterials, medical implants, and biosensors where biocompatibility is required.…”
Section: Introductionmentioning
confidence: 99%